Humanization of the place in the novel (Holler Habibati) to abdulbaki Joseph - المدرس المساعد حسين مجيد حسين (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This paper studies the use of personification in Abdulbaqi Yousuf’s novel, Hawler My Beloved. In this novel, personification is a technical and artistic mean utilized to transform non-human entities, such as place itself, into human characters. The setting of the novel is transferred from only being a traditional atmosphere of narration, time, characterization, or storytelling to a human-like existence that perceives what goes around. The humanly perceptions assign the positions and significances of time, places, events, things and people. Personification is embodied in the perspectives of body and psychology, where place itself shows itself as a body that carries out various human actions. These human actions incorporate to different cultural and social dimensions that are clearly reflected in the lives of the humans. Besides, in this novel, several dimensions of human inward feelings and senses are present.